Welfare Reform, Accumulation and Social Exclusion in the United Kingdom - Chris Grover (Social Work & Society, 2006)
Jordan (2000) notes how while there is a possible confluence between social work practice and New Labour's social inclusion agenda, social work has been excluded from it. The explanation for this lays in the narrow definition, focusing almost entirely on exclusion from paid employment that frames political concerns with social exclusion in the UK. However, the policies designed to tackle social exclusion even in this rather narrow approach should be of concern to social work because it is possible that they will exacerbate rather than tackle the exclusion that many social work clients face. To explore these issues this paper draws upon Penna's (2001) argument that there is a tension between the desire to tackle social exclusion at a national level and global economic governance that constructs neo-liberalism as being the only way forward to economic prosperity and stability because the operation of neo-liberal political economy creates social exclusion. The paper examines these tensions by focusing upon what Adler (2004) identifies as a new model - the employment model - for the relief of poverty in the UK. The paper discusses the antecedents of the employment model in the shift from Keynesianism to neo-liberalism. The paper demonstrates that the employment model is concerned with regulating a number dilemmas related to labour power and the wage relation that have emerged from the acceptance of the global neo-liberal economy as being the only viable economic paradigm. It then goes on to discuss the contingent nature of this process, highlighting the contradictions raised by the employment models in terms of economic development and the tackling of social exclusion.